Sentidos sobre la infancia en contextos rurales: El caso del barrio Patután de Cotopaxi. - Zongor Quizpi, Jimena Fernanda (2020)
The issue of what it means to be a child has been a subject of discussion throughout history, but within the field of communication there is deficient information. For this reason, the objective of this project is to identify how the senses are constructed about childhood in the adult and child population of the Patután neighborhood, located in the Cotopaxi province. The methodological strategy was based on a qualitative approach using the life history method. Five families participated, among parents and children; in the case of adults, in-depth interviews were conducted using questions and answers instrument; and in the case of children, the weekly diary method was used to record their daily activities. Among the main results, it was detected that the senses about childhood are built according to the parenting styles experienced by the parents and that they are transmitted to their children in different ways. In some cases, parents signify their own childhood experience; and in other cases, they reproduce the meanings of their childhood in the education of their children. In summary, it is proposed that the meanings about childhood are elaborated, mainly, from the maternal figure, and the importance of participation in spaces external to the family for the experience of childhood is also proposed.